Italian Clinical Practice Guidelines on Cholangiocarcinoma – Part II: Treatment - Alvaro, Domenico; Hassan, Cesare; Cardinale, Vincenzo; Carpino, Guido; Fabris, Luca; Gringeri, Enrico; Granata, Vincenza; Mutignani, Massimiliano; Morement, Helen; Giuliante, Felice; Guglielmi, Alfredo; Ridola, Lorenzo; et al. (Digestive and liver disease, 2020)
Currently, the only curative treatment for cholangiocarcinoma (CCA) is surgical resection, though this treatment is possible in less than 40% of patients. However, recent improvements in preoperative management have led to a higher number of patients who are candidates for this procedure. For unresectable patients, progress is ongoing in terms of locoregional and chemoradiation treatments and target therapies, especially in the definition of patient selection criteria. This is the second part of the Italian CCA guidelines, dealing with CCA treatment, that have been formulated in accordance with Italian National Institute of Health indications and developed according to the GRADE method and related advancements.